2021
DOI: 10.3390/plants10061234
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory and the Antinociceptive Effects of Mixed Agrimonia pilosa Ledeb. and Salvia miltiorrhiza Bunge Extract

Abstract: Arthritis is a common condition that causes pain and inflammation in a joint. Previously, we reported that the mixture extract (ME) from Agrimonia pilosa Ledeb. (AP) and Salvia miltiorrhiza Bunge (SM) could ameliorate gout arthritis. In the present study, we aimed to investigate the potential anti-inflammatory and antinociceptive effects of ME and characterize the mechanism. We compared the anti-inflammatory and antinociceptive effects of a positive control, Perna canaliculus powder (PC). The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(71 reference statements)
1
10
0
Order By: Relevance
“…In addition, LPS-induced oxidative stress was confirmed by reducing TAC and NO elevation in lung tissues. APEE treated group restored TAC levels and decreased NO levels and these antioxidant effects are in accordance with other studies [40,43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, LPS-induced oxidative stress was confirmed by reducing TAC and NO elevation in lung tissues. APEE treated group restored TAC levels and decreased NO levels and these antioxidant effects are in accordance with other studies [40,43].…”
Section: Discussionsupporting
confidence: 92%
“…The underlying mechanisms of the anti-inflammatory effect of APEE may be due to their flavonoids which were proven previously to have strong anti-inflammatory effects. According to data obtained from LC/MS, it is concluded that APEE contains numerous flavonoids including but are not limited to quercetin, isoquercitrin, hesperetin, luteolin, rutin, kaempferol, apigenin, and esculin and all have strong anti-inflammatory and antioxidant effects [40,43,44] which may explain the promising protective effects of APEE in LPS-induced ALI due to its enormous components of valuable flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…For large data sets, the “big data + complex model” mode can effectively improve learning efficiency [ 19 ]. Therefore, this study introduces the Mini-Batch gradient descent algorithm to optimize the unsupervised learning model in the processing of large data sets.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to control animals in a cisplatin-induced neuropathic model, Agrimonia eupatoria extract showed significant differences and superior activity in the pin-prick test, plantar test, and paw-withdrawal threshold test. A recent study reported on Agrimonia eupatoria extract showed that its analgesic molecular mechanisms were associated with the downregulation of TNF-α and mitogen-activated protein kinase (MAPK) protein expression, as well as with the inhibition of the release of NO, prostaglandin E2 (PGE2), leukotriene B4 (LTB4), and interleukin 6 (IL-6) ( Feng et al, 2021 ). Therefore, Agrimonia eupatoria may be deemed a potential therapeutic agent for cisplatin-induced neuropathic pain.…”
Section: Plant-derived Medicines Limiting Platinum-induced Peripheral Neurotoxicitymentioning
confidence: 99%